The interaction of the real and digital sectors of economy - Ukolov, Vladimir F.; Abramov, Valery L.; Kalinina, Irina; Guseva, Maria G. (Opción, 2019)
The article is aimed at identifying the basic theoretical fundamentals for building interaction of the real and digital economic sectors. The leading method for studying this problem is consideration of the processes of interaction between the real and digital sectors of the economy in close interconnection at different time periods. As a result, the modifications in digital technologies of economic interaction outrun the transformation of the humans who use it in casual activities. In conclusion, activation is a significant non-material factor affecting the integrity of the economy and affecting the quantitative and qualitative characteristics of the socio-economic development of territories.